(E.M.G) Some muscles and angles performance in the stages of up and down the slopes (8º) - Almujamay, Ahmed Sabea Atea; Abdul Razzaq, Zinah Abdul Salam (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to know the muscular activity and the performance angles that are appropriate for uphill and downhill of the slopes at (8°), therefore, the researchers opine to do this study to know the fact of this discussion that they will find through the magnitude of the working muscles’ participation during the two stages, that’s all by the electrical muscle activity device (EMG) and kinematic analysis, the remaining muscles are involved and used in the research to increase the space of the study to discover other muscles that might participate and have benefit by developing them during the giving of this type of training. The problem of the research came through the questioning of some training specialists, that uphill training improves and develops the step of the runners, while during downhill training the speed and frequency of the runners are developed. This leads us to the training fact of muscles’ development by choosing the type of slope training and whether it’s uphill or downhill. The research sample represented by (6) speed runners (100) m in Track and field, season (2018-2019), the experiment occurred on one of the slopes that exist in the College of Physical Education and Sports Science/ University of Baghdad. The researchers extracted (Mean) by the program (SPSS) of processing data. The researchers concluded that the training of the uphill slope develops the length of the step of running, while the downhill drill development of the step frequency.